Finite Element Analysis of Magnetorheological Brake using ANSYS (International Journal of Current Engineering and Technology, 2015)
The aim of this paper is to understand the electromagnetic action in a magnetorheological (MR) brake (MRB) system using finite element method. MR brake system consists of rotary disks immersed in a MR fluid and enclosed in an electromagnet. The torque exerted by MR fluid on the rotary disks is a function of magnetic field created by electric current passing through the electromagnet. To estimate the braking torque, under various operating conditions, an APDL code has been developed. Based on the parametric study, decisions on materials for various components of the MR brake have been made. Finally, a procedure to design a MR brake has been recommended.
Keywords: MR fluid; MR brake; Multi disk MR Brake; Electromagnetic simulation; Finite element analysis